Chlorhexidine versus povidone-iodine for surgical site infection prevention: an updated meta-analysis and trial sequential analysis of randomized controlled trials - Yang, Shengyi; Li, Zhenwei; Wu, Feiyu; Sun, Liyuan; He, Yulu; Wang, Changxian (Frontiers in Medicine, 2025)
BackgroundChlorhexidine (CHX) and povidone-iodine (PVI) are the most commonly used antiseptic agents for preoperative skin preparation to prevent surgical site infections (SSIs). This meta-analysis aimed to determine the superior agent between them for SSI prevention.MethodsWe conducted a systematic review and meta-analysis in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A comprehensive search of electronic databases (PubMed, Web of Science, Embase, and Cochrane Central Register of Controlled Trials) was performed from inception to 1 May 2025, to identify relevant randomized controlled trials (RCTs). Heterogeneity was assessed using the chi-squared (Q) test and the I2 statistic. A random-effects model was applied when significant heterogeneity was present. The robustness of the findings was evaluated using trial sequential analysis (TSA) with a random-effects model. All statistical analyses were performed using Review Manager.ResultsA total of 32 high-quality RCTs, involving 29,748 participants, were included. The pooled analysis using a random-effects model demonstrated that CHX was significantly more effective than PVI in preventing SSIs (RR = 0.83, 95% CI 0.72–0.95, p = 0.009). Subgroup analysis by wound classification revealed that CHX was superior to PVI in clean-contaminated surgeries (11 RCTs; RR = 0.75, 95% CI 0.62–0.92, p = 0.004), but no significant difference was observed in clean surgeries (20 RCTs; RR = 0.90, 95% CI 0.67–1.20, p = 0.46). Further stratification by SSI type indicated that CHX significantly reduced the risk of superficial incisional SSIs (18 RCTs; RR = 0.82, 95% CI 0.69–0.98, p = 0.03), but not deep incisional SSIs (16 RCTs; RR = 0.95, 95% CI 0.76–1.18, p = 0.63) or organ-space SSIs (11 RCTs; RR = 1.13, 95% CI 0.89–1.42, p = 0.32). Additionally, CHX was associated with a significantly lower risk of bacterial decolonization (RR = 0.38, 95% CI 0.26–0.57, p < 0.001) and febrile episodes (RR = 0.57, 95% CI 0.35–0.92, p = 0.02) compared to PVI. The TSA confirmed the robustness of these findings, indicating that the cumulative evidence was sufficient and conclusive.ConclusionCHX-based antiseptics are more effective than PVI-based ones in preventing overall SSIs, particularly in clean-contaminated procedures. The superiority of CHX is primarily evident in reducing superficial incisional SSIs, with no significant advantage observed for deep incisional or organ-space SSIs.